Cardiac involvement in sarcoidosis: Evolving concepts in diagnosis and treatment - Lynch III, Joseph P; Fishbein, Michael C; Bradfield, Jason S; Belperio, John A (Journal of Cardiovascular Medicine and Cardiology, 2021)
Clinically evident cardiac involvement has been noted in at least 2 to 7% of patients with sarcoidosis, but occult involvement is much higher (> 20%). Cardiac Sarcoidosis (CS) is often not recognized as an antemortem, as sudden death may be the presenting feature. Cardiac involvement may occur at any point during the course of sarcoidosis and may occur in the absence of pulmonary or systemic involvement. Sarcoidosis can involve any part of the heart. The prognosis of CS is related to the extent and site(s) of involvement. Most deaths due to CS are due to arrhythmias or conduction defects, but granulomatous infiltration of the myocardium may cause progressive and ultimately lethal cardiomyopathy. The definitive diagnosis of isolated CS is difficult and the yield of Endomyocardial Biopsies (EMB) is low. Treatment of CS is often warranted even in the absence of histologic proof. Radionuclide scans are integral to the diagnosis. Gadolinium-enhanced cardiac magnetic imaging scans and 18Fluorodeoxyglucose (18FDG)-Positron Emission Tomography (PET) are the key imaging modalities to diagnose CS. The prognosis of CS is variable, but mortality rates of untreated CS are high. Randomized therapeutic trials have not been done, but corticosteroids (alone or combined with additional immunosuppressive agents) are the mainstay of therapy. Additionally, anti-arrhythmic agents and therapy for heart failure are often required. Because of the potential for sudden cardiac death, an Implantable Cardioverter-Defibrillator (ICD) should be placed in any patient with CS and serious ventricular arrhythmias or heart block and should be considered for cardiomyopathy. Cardiac transplantation is a viable option for patients with end-stage CS refractory to medical therapy.